2020
DOI: 10.1111/jfpe.13360
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of anthocyanins from purple rice bran and effect of hydrocolloids on its stability

Abstract: The degradation kinetics of total anthocyanin, cyanidin‐3‐glucoside (C3G), and peonidin‐3‐glucoside (P3G) from purple rice bran were investigated in various pH and temperature conditions. The effect of hydrocolloids on the stability of anthocyanins was also determined. The degradation kinetics was studied in a pH range of 2–8 and temperatures ranging from 60 to 90°C. At pH 2, the total anthocyanin (2.21 × 10−4 min−1), C3G (1.44 × 10−4 min−1), and P3G (1.38 × 10−4 min−1) showed the lowest degradation rate. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Additionally, the k and t 1/2 values increased and declined, respectively, in conjunction with a higher drying temperature ( Table 2 ). Similar results were evident in almost all studies on heat-induced anthocyanin degradation ( Das et al, 2020 , Sun et al, 2020 ). Accordingly, it can be concluded that the molecular structure and temperature of drying co-regulate the degradation rate of anthocyanins in RC during AIJD.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, the k and t 1/2 values increased and declined, respectively, in conjunction with a higher drying temperature ( Table 2 ). Similar results were evident in almost all studies on heat-induced anthocyanin degradation ( Das et al, 2020 , Sun et al, 2020 ). Accordingly, it can be concluded that the molecular structure and temperature of drying co-regulate the degradation rate of anthocyanins in RC during AIJD.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies found that cyanidin O-syringic acid was the most abundant anthocyanin in red-and purple-colored vegetables and fruits, such as kiwifruit, kiwiberry, and radishes (Montefiori et al 2009;Yu et al 2020;Zhang et al 2020). However, contrary to previous studies, cyanidin 3-O-glucoside and peonidin 3-O-glucoside were the two major anthocyanins found in the pericarp of black rice (Lee 2010;Shao et al 2013;Das et al 2020).…”
Section: Comprehensive Comparison Of the Metabolism Of Flavonoids In ...contrasting
confidence: 99%
“…The results reported above have been corroborated by other studies regarding the degradation of anthocyanins at high temperatures (from 60 to 95 °C). ,, In summary, the rates of these degradations are monoexponential, with lifetimes ranging from approximately 1 to 5 h. The degradation rate increases with the increase of temperature and pH (up to pH = 6).…”
Section: Degradation Of Anthocyanins and Related Compoundsmentioning
confidence: 99%